Adapting Open Innovation Model in Supplier Qualification Programs - Gályász, József; Darnai, Balázs; Antal, József (International Journal of Engineering and Management Sciences, 2017)
The development of innovative models fundamentally contribute to the changing the way of thinking in business context. Today, in this process, the impact of open innovation model is a kind of paradigm shift. The contents of this change has been mostly clear in the field of context of product-, innovation and technology, but not onm the field of organizational and management innovations. In this study, we sought to answer that in the case of knowledge transfer’s special field –the programs of suppliers - how to apply the principles of open innovation and how this may have positive effects. The motivation behind, was to look for commonly used models for the SME sector, that is fundamentally linked to large enterprises as suppliers, characterized by increasingly rapid technological development ecosystem to collaborate.